Comparative Testing of Filled Plastic Compounds : A Theoretical Analysis and Practical Measurements - Catrysse, J.; Delesie, M. (9th International Zurich Symposium and Technical Exhibition on Electromagnetic Compatibility, 1991)
Shielding of electronic circuits and systems against electromagnetic emission and susceptibility becomes a necessity in modern system design. Not only because there are legal limitations and standards, but also because the interference between the systems themselves is the origin of many problems. Conductive plastics have a very important role in the design of the housings for new electronic systems. They are specified on the basis of different test methods. In this paper, the measurements results using different test methods are given and discussed for conductive plastics filled with stainless-steel fibers.